An Analysis of the Trend of Linezolid Utilization in E Hospital from 2019 to 2023 - Son Nhat, Bui; Hong Ngoc, Vu Thi; Nghia, Nguyen Trung; Anh, Le Tuan (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 41 No 4DO - 10.25073/2588-1132/vnumps.4794, 2025)
Abstract: This study aimed to quantitatively analyze linezolid consumption at E Hospital from 2019 to 2023. Subjects and Methodology: Data on antibiotic utilization of linezolid and patient hospitalization days from 2019 to 2023 were extracted from the iSofH software system of E Hospital. The study employed a quantitative analysis based on Defined Daily Dose (DDD) and DDD per 100 patient-days for antibiotics used in clinical departments and the entire hospital, analyzed monthly and annually over the 2019–2023 period. Results: Linezolid utilization of the hospital decreased significantly in 2023 compared to previous years (0.17 DDD/100 bed days compared to 1.06 and 0.78 DDD/100 bed days in 2021 and 2022, respectively), while vancomycin consumption surpassed linezolid for the first time in 2023 (0.45 DDD/100 bed days) and showed an increasing trend during the 2019 – 2023 period. The Intensive Care unit (ICU) of the hospital utilized the largest amount of linezolid from 2019 to 2023, followed by the Department of Trauma Surgery (A9). The utilization of linezolid in the Department of Orthopedic Surgery and Sports Medicine, once the third highest from 2019 to 2022 at 1.54 DDD/100 bed days, sharply declined to a meager amount of 0.03 DDD/100 bed days. Analyses of the impact of the regulation process via ARIMA modeling showed a general immediate decline in linezolid use in the hospital. The ICU showed an increasing slope in consumption in the months following January 2023. Conclusions and Recommendations: The implementation of the linezolid use regulation process through clinical pharmacy activities has shown remarkable initial results in optimizing linezolid utilization across the hospital. Sustaining and improving on these activities should be crucial to promote the rational use of "Reserve" antibiotics at E Hospital. Keywords: Linezolid, antibiotic, utilization, DDD, gram-positive.